2021
DOI: 10.3389/fcell.2021.746714
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA Small Nucleolar RNA Host Gene 14, a Promising Biomarker and Therapeutic Target in Malignancy

Abstract: Small nucleolar RNA host gene 14 (SNHG14) is a long non-coding RNA found to be overexpressed in various types of cancers. Moreover, the expression level of SNHG14 was closely associated with multiple clinicopathological characteristics such as prognosis, tumor differentiation, TNM stage, and lymph node metastasis. Functionally, gain- and loss-of-function of SNHG14 revealed that overexpressed SNHG14 promoted cancer cell viability, invasion, and migration, whereas its down-regulation produced the opposite effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 92 publications
(132 reference statements)
0
7
0
Order By: Relevance
“…This is the first study analyzing the relationship between the expression level of SNHG14 and the prognosis and clinical characteristics among cancer patients. Shen et al (2021) previously described the expression profile, biological function, and molecular mechanism of SNHG14 in cancer, facilitating a molecular basis for future clinical application of SNHG14. We conducted a meta-analysis to evaluate the association between SNHG14 expression, OS, and the clinicopathological significance of different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study analyzing the relationship between the expression level of SNHG14 and the prognosis and clinical characteristics among cancer patients. Shen et al (2021) previously described the expression profile, biological function, and molecular mechanism of SNHG14 in cancer, facilitating a molecular basis for future clinical application of SNHG14. We conducted a meta-analysis to evaluate the association between SNHG14 expression, OS, and the clinicopathological significance of different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG14 RNA is overexpressed in multiple cancer types, including non-small cell lung cancer, hepatocellular carcinoma, glioma, breast cancer, ovarian cancer, and colorectal cancer, among others [34]. These tissues generally have little to no expression of this lncRNA in their normal state.…”
Section: Expression Of Snhg14 Rnamentioning
confidence: 99%
“…11 The lncRNA SNHG14, also known as UBE3A-ATS, located on human chromosome 15q11.2, has been widely studied as an oncogene. 12 Knockout of lncRNA SNHG14 can significantly inhibit the survival and migration of gastric cancer SGC-7901 cells, and promote cell apoptosis. 13 Zhu et al claimed that silencing lncRNA SNHG14 could restrain lipopolysaccharidestimulated cell apoptosis and inflammatory response in an acute lung injury cell model.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al reported that lncRNA ANRIL up‐regulated the expression of BRCC protein by targeting miR‐122‐5p, and so activating NLRP3 inflammatory bodies and accelerating the development of uric acid‐induced inflammation, and promoting the occurrence and development of gouty nephropathy 11 . The lncRNA SNHG14, also known as UBE3A‐ATS, located on human chromosome 15q11.2, has been widely studied as an oncogene 12 . Knockout of lncRNA SNHG14 can significantly inhibit the survival and migration of gastric cancer SGC‐7901 cells, and promote cell apoptosis 13 .…”
Section: Introductionmentioning
confidence: 99%